Two decades of American feminist criticism, 2.5.1989. University of Vienna, Austria - Gjurgjan, Ljiljana Ina (1989)
This lecture has looked into the shift from the homogenised ideology of early feminism to the new awareness of feminist differences, theoretical as well as ideological (ecriture feminine, gender studies, Afro-American studeis). In doing so the lecture attempted to outline the relationship between feminist criticism, poststructuralist thought, cultural and gender studies and postcolonial criticism.
ENG